Exchange Rate Movements and Their Impact on Trade and Investment in the APEC Region - Ito, Takatoshi (Occasional Papers; Occasional Paper, 1996)
The 18 members of the Asia-Pacific Economic Cooperation Council (APEC) encompass not only a wide geographic area but also broad differences in stages of economic development, including among them some of the fastest- growing economies in the world. Such rapid growth has been ficilitated by high levels of investment and trade, international linkages, and, in most APEC economies, macroeconomic policies that have sustained growth while not sparking excessive inflation. This study offers insights about how medium and long-term changes in real exchange rates have affected international (and intra-APEC) trade and investment in the region.